2019
DOI: 10.1111/adb.12816
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of the histone demethylase KDM6B in alcohol dependence is associated with epigenetic regulation of inflammatory signaling pathways

Abstract: Epigenetic enzymes oversee long-term changes in gene expression by integrating genetic and environmental cues. While there are hundreds of enzymes that control histone and DNA modifications, their potential roles in substance abuse and alcohol dependence remain underexplored. A few recent studies have suggested that epigenetic processes could underlie transcriptomic and behavioral hallmarks of alcohol addiction. In the present study, we sought to identify epigenetic enzymes in the brain that are dysregulated d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 78 publications
1
25
0
Order By: Relevance
“…H3K27me3 was enhanced via recruitment of EZH2 at the BDNF and ARC loci in the amygdala of the alcoholic postmortem brain, with the corresponding decrease in Arc and BDNF expression in the early-onset AUD postmortem brain amygdala [ 181 ]. Consistent with the above observations, increased KDM6B, which regulates H3K27me3 levels, was found in individuals with AUD in the anterior cingulate cortex [ 182 ]. These limited studies pinpoint the participation of both H3K4me3 and H3K27me3 marks’ mediated gene regulation in human AUD’s pathophysiology.…”
Section: Alcohol Use Disorders (Aud)supporting
confidence: 73%
“…H3K27me3 was enhanced via recruitment of EZH2 at the BDNF and ARC loci in the amygdala of the alcoholic postmortem brain, with the corresponding decrease in Arc and BDNF expression in the early-onset AUD postmortem brain amygdala [ 181 ]. Consistent with the above observations, increased KDM6B, which regulates H3K27me3 levels, was found in individuals with AUD in the anterior cingulate cortex [ 182 ]. These limited studies pinpoint the participation of both H3K4me3 and H3K27me3 marks’ mediated gene regulation in human AUD’s pathophysiology.…”
Section: Alcohol Use Disorders (Aud)supporting
confidence: 73%
“… 25 The highly expressed KDM6B was observed in the alcoholic brain of rats, while the KDM6B knockdown resulted in repressed inflammation in microglial cells through the inhibition of IL-6 induction. 26 Hence KDM6B silencing has a significant protective role against ischemic brain injury through its ability to alleviate neurological deficits and suppress inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…In the study of Domingues and cols in 2016, 13 tor role of ethanol is widely recognized 26,27 ; previous studies have shown that humans with constant alcohol use exhibit chronic alterations in gene expressions. 28 Furthermore, this disorder has been related with higher aldosterone concentrations, 29 and this hormone plays a key regulator role in maintaining blood pressure and the body fluid balance through the electrolyte homeostasis. 30,31 The effects of high aldosterone concentrations include an increase in urinary excretion, 32 which can be responsible for the higher fluoxetine clearance, and its consequent lower concentration.…”
Section: Discussionmentioning
confidence: 99%